Adverse association of epicardial adipose tissue accumulation with cardiac function and atrioventricular coupling in postmenopausal women assessed by cardiac magnetic resonance imaging - Huang, Shan; Shi, Ke; Jiang, Li; Ren, Yan; Wang, Jin; Yan, Wei-Feng; Qian, Wen-Lei; Li, Yuan; Yang, Zhi-Gang (Frontiers in Cardiovascular Medicine, 2022)
Background This study aims to investigate the association of epicardial adipose tissue (EAT) accumulation with cardiac function and atrioventricular coupling in a cohort of postmenopausal women assessed by cardiac magnetic resonance imaging (CMR). Materials and methods Overall, 283 postmenopausal women (mean age 61.5 ± 9.1 years) who underwent CMR examination were enrolled. Participants were classified into four groups by the quartile of EAT volume. EAT volume was quantified on short-axis cine stacks covering the entire epicardium. CMR-derived cardiac structure and function, including left atrial (LA)- volume, emptying fraction, deformation, and left ventricular (LV)- mass, volume, ejection fraction, and deformation, were compared among the four groups of graded EAT volume. Results Left ventricular mass (LVM) and LV remodeling index were both increased in the group with the highest EAT volume, compared to those in the lowest quartile (p = 0.016 and p = 0.003). The LV global longitudinal strain (LV-GLS), circumferential strain (LV-GCS), and LA- reservoir strain (LA-RS), conduit strain (LA-CS), and booster strain (LA-BS), were all progressively decreased from the lowest quartile of EAT volume to the highest (all p < 0.05). Multivariable linear regression analyses showed that EAT was independently associated with LV-GLS, LA-RS, LA-CS, and LA-BS after adjusting for body mass index and other clinical factors. Conclusion Epicardial adipose tissue accumulation is independently associated with subclinical LV and LA function in postmenopausal women. These associations support the role of EAT in mediating deleterious effects on cardiac structure and function.